Optimized quercetin-loaded glycerohyalurosome hydrogel: an innovative nanoplatform for enhanced wound healing - Walaa Abualsunun; Amerh Aiad Alahmadi; Bayan A. Eshmawi; Osama A. A. Ahmed; Alaa Sirwi; Mahmoud A. Elfaky; Sarah O. Alreeshi; Ibtisam A. Alzahrani; Ibtihal A. Almutairi; Rumaysaa M. Gurunfula; Omaima N. Elgazayerly; Shaimaa M. Badr-Eldin (Future Journal of Pharmaceutical Sciences)
Abstract Background Lipidic nanovesicular systems have attracted researchers’ interest for more effective cutaneous delivery and topical pharmacological efficacy. Quercetin (QUT), a polyphenolic flavonoid known for its antioxidant and anti-inflammatory activity, suffers from poor solubility and bioavailability. The aim of this research was to develop an optimized hydrogel formulation comprising QUT-loaded hyaluronic acid (HYA)-modified glycerosomes (glycerohyalurosomes, GHEs) for effective wound management. A combination of glycerol (GLY) and HYA is being used to provide flexibility to the vesicles for better delivery through the skin; these compounds have been reported to provide benefits for wound healing. Results D-optimal design suggested fifteen formulations of QUT-GHEs which were prepared using a modified thin-film hydration method. Results showed that particle sizes ranged from 162.33 to 478.49 nm and zeta potential from −57.8 to −18.8 mV. Transmission electron microscopy confirmed successful loading of the drug into the vesicles. QUT-GHEs were integrated into hydrogel (QUT-GHE-GEL) using 1.5% hydroxypropyl methylcellulose. The pH of the QUT-GHE-GEL was recorded as 5.9 ± 0.03, which is acceptable in wound healing. In vivo studies performed on Wistar rats showed that QUT-GHE-GEL accelerated the wound-healing process compared to the untreated control and marketed product (MP)-treated groups, where a significantly higher wound contraction was observed. Histopathological examination of wound tissues revealed that QUT-GHE-GEL-treated and MP-treated groups exhibited newly sprouted capillaries and enhanced fibroblast development. Conclusions Thus, the suggested QUT-GHE-GEL formulation shows promise for effective wound-healing management. QUT-GHE-GEL enhances wound contraction and fosters tissue regeneration while modulating inflammation. The results indicate that QUT-GHE-GEL proves a prospective therapeutic option for wound care applications.